2019
DOI: 10.3390/su11020517
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the Opportunities and Challenges of Green Finance in Italy: An Analysis of the Biomass Production Sector

Abstract: The present paper provides empirical evidence of the opportunities and challenges surrounding green finance (GF), looking at the financial issues that might prevent the investment decisions of green companies. To this end, we explore the case of Italian biomass producers by means of a discourse analysis supported by a survey administered to a pool of experts. Although our findings suggest that GF provides an opportunity for achieving environmentally sustainable innovation pathways, experts recognize that it do… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
62
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 123 publications
(74 citation statements)
references
References 31 publications
(31 reference statements)
2
62
0
Order By: Relevance
“…For example, they may increase the use of forests and agricultural land, potentially beyond planetary boundaries, producing erosion and contamination (Purkus, Hagemann, Bedtke, & Gawel, 2018). In restraining such pressures, a transition towards innovative and sustainable technologies should be sensitive to the utilization of renewable resources (Falcone & Sica, 2019). Thus, sustainable innovation for the bio-economy should ensure: overall competitiveness with respect to traditional fossil-based resources, low environmental impacts, and adequate social acceptability.…”
mentioning
confidence: 99%
“…For example, they may increase the use of forests and agricultural land, potentially beyond planetary boundaries, producing erosion and contamination (Purkus, Hagemann, Bedtke, & Gawel, 2018). In restraining such pressures, a transition towards innovative and sustainable technologies should be sensitive to the utilization of renewable resources (Falcone & Sica, 2019). Thus, sustainable innovation for the bio-economy should ensure: overall competitiveness with respect to traditional fossil-based resources, low environmental impacts, and adequate social acceptability.…”
mentioning
confidence: 99%
“…Sustainability 2020, 12, 540 2 of 20 investment faces many challenges in the rapid transformation of the economy and society to meet the Paris 1.5 °C climate target. Green finance provides not only an opportunity for achieving environmentally sustainable innovation pathways but it also faces some institutional and financial criticalities such as uncertainty about public policies, minimum involvement of financial suppliers, short-term financial instruments, and the knowledge gap of financial options and technical expertise within firms [7]. In Asia, Japan is in the leading position regarding socially responsible funds investment.…”
Section: Introductionmentioning
confidence: 99%
“…Sustainable investment faces many challenges in the rapid transformation of the economy and society to meet the Paris 1.5 °C climate target. Green finance provides not only an opportunity for achieving environmentally sustainable innovation pathways but it also faces some institutional and financial criticalities such as uncertainty about public policies, minimum involvement of financial suppliers, short-term financial instruments, and the knowledge gap of financial options and technical expertise within firms [7]. Though significant developments have been recorded in greening the economy, the United Nations Environment Programme (UNEP) estimates that the annual investment necessary to deliver a green economy over the 2010-2050 period will be approximately 2% of global GDP [6].…”
Section: Introductionmentioning
confidence: 99%
“…The United Nations Environmental Program (2011) found that the movement toward a low carbon and climate resilient economy required investment in green sectors of business [27]. To place this within the context of green economies, such as biomass production, investment in renewable energy, or other CE related industries, e.g., making compost from green waste in Guatemala, the necessary investment worldwide will equal 2% of the GDP between 2010 and 2050 [28]. This is a significant sum of financial investment, but it is necessary to slow the impacts of climate change on a worldwide scale.…”
Section: Introductionmentioning
confidence: 99%
“…Considering this, how does CE fit in within the context of this paper-making compost-and how does it begin to form a guiding principle for local municipal governments to follow? While some countries have adopted a top-down centralized approach, such as China [28], others emphasize a more localized bottom-up policy direction [29], more typically used in municipal and regional planning. Perhaps the difference is again associated with the scale of CE.…”
Section: Introductionmentioning
confidence: 99%